2021
DOI: 10.3389/fpsyg.2021.741585
|View full text |Cite
|
Sign up to set email alerts
|

Don’t Call It Smart: Working From Home During the Pandemic Crisis

Abstract: The recent COVID-19 pandemic and related social distancing measures have significantly changed worldwide employment conditions. In developed economies, institutions and organizations, both public and private, are called upon to reflect on new organizational models of work and human resource management, which - in fact - should offer workers sufficient flexibility in adapting their work schedules remotely to their personal (and family) needs. This study aims to explore, within a Job Demands-Resources framework,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 106 publications
(126 reference statements)
3
33
0
Order By: Relevance
“…Indeed, the implementation of smart working requires adequate management policies with particular attention to the reorganization of work and personnel management [ 3 , 72 ]. It would be necessary for organizations to utilize human resource management more effectively, implementing a more inclusive and differentiated approach to support employees, and thinking about the workers’ different needs to better balance work and private life [ 30 ]. The digitization of work processes and tools is not a mechanical and automatic process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the implementation of smart working requires adequate management policies with particular attention to the reorganization of work and personnel management [ 3 , 72 ]. It would be necessary for organizations to utilize human resource management more effectively, implementing a more inclusive and differentiated approach to support employees, and thinking about the workers’ different needs to better balance work and private life [ 30 ]. The digitization of work processes and tools is not a mechanical and automatic process.…”
Section: Discussionmentioning
confidence: 99%
“…Workers, after all, must be adequately trained and have adequate resources to be able to offer good performance [ 38 ]. The literature [ 30 ] about the JDR Model and smart working demonstrated that job demands (workload and social isolation), organizational job resources (perceived organizational support), and individual job resources (self-efficacy, vision about the future, and commitment to organizational change) have affected workers’ quality of life during the pandemic. Whoever manages the human resources of an organization is therefore called on to implement new practices, aimed at reinforcing the workers’ engagement even when the work methods change, motivating them to adopt proactive behaviors and positive attitudes, achieving results in line with the expectations of the organization [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has reported that high POS relieves work stress, anxiety, depression, and burnout; it increases job satisfaction, organizational commitment, and work productivity. [3][4][5][6][7][8][9][10] Increasing POS would, therefore, be of great significance to employees and organizations-even under the special circumstances of the pandemic. POS has been found to be increased by several antecedent factors.…”
Section: Introductionmentioning
confidence: 99%
“…Though there is plenty of discussion about the effect of COVID-19 on knowledge workers in general (Wu and Chen 2020 ; Barbieri et al 2021 ; Gibbs et al 2021b ; Kniffin et al 2021 ; Laumer and Maier 2021 ; Madariaga et al 2021 ), and studies which aim to explore impacts in specific industries (Brewin 2020 ; Pamidimukkala and Kermanshachi 2021 ; Škare et al 2021 ), we could not find evidence in the previous studies to pinpoint the simple but challenging fact that we uncovered in our interviews: product design is a mix of Tangible and Intangible Design activities, and while is it possible to complete many Intangible Design activities remotely, it is near impossible to complete the Tangible Design activities from home. Managers should consider implementing tools that allow employees to replicate Tangible activities in the digital world and collaborate seamlessly from a distance.…”
Section: Resultsmentioning
confidence: 99%